2017
DOI: 10.18697/ajfand.77.15320
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality and safety of raw and pasteurized milk marketed in and around Nairobi region

Abstract: The microbiological quality of raw and pasteurized milk marketed in Nairobi and its environs was determined. Milk samples were collected randomly at milk selling points from three market areas: rural (Kiambu/Ngong), urban (East/West of Tom Mboya street) and slum (Kibera/Mathare). Samples were analysed for titratable acidity, total viable count (TVC), Staphylococcus aureus, coliforms and Enterobacteriaceae. Titratable acidity was determined using titration method, while TVC, S. aureus and Enterobacteriaceae wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
(21 reference statements)
3
16
1
Order By: Relevance
“…This cooperative received milk from farmers and held it without cooling for a few hours before it was delivered to the processors still without refrigeration, a practice which results in rapid multiplication of bacteria. This study agrees with one done by Wanjala et al, (2017) where mean S. aureus counts were 5.83, 6.32, and 5.82 log 10 cfu/ml in raw milk collected from Kenyan rural, urban and slum areas respectively all exceeding the set standards. However, the results in this study were higher than those found in a study done in Bangladesh where S. aureus counts in raw milk samples from farms, chilling centres, and traders were 2.90, 2.77 and 2.78 log cfu/ml respectively (Islam et al 2016).…”
Section: Staphylococcus Aureussupporting
confidence: 91%
“…This cooperative received milk from farmers and held it without cooling for a few hours before it was delivered to the processors still without refrigeration, a practice which results in rapid multiplication of bacteria. This study agrees with one done by Wanjala et al, (2017) where mean S. aureus counts were 5.83, 6.32, and 5.82 log 10 cfu/ml in raw milk collected from Kenyan rural, urban and slum areas respectively all exceeding the set standards. However, the results in this study were higher than those found in a study done in Bangladesh where S. aureus counts in raw milk samples from farms, chilling centres, and traders were 2.90, 2.77 and 2.78 log cfu/ml respectively (Islam et al 2016).…”
Section: Staphylococcus Aureussupporting
confidence: 91%
“…The SPC of raw cow's milk produced in the study area was far above the east African standard, since the minimum quality standard plate count value of Ethiopia is 6.3 log 10 CFU/ml or 2x10 6 [33]. On the other hand, relatively lower SPC (6 log 10 CFU/ml) was reported in and around Nairobi, Kenya [34]. Based on Kurwijila et al [35], raw milk containing greater than 7 log 10 CFU/ml is categorized as poor grade.…”
Section: Standard Plate Countmentioning
confidence: 95%
“…Milk samples were collected early in the morning up to mid-morning. A minimum of sixty-four milk samples were required to give a representative sample size for representing a category of sampled milk, raw or pasteurized [12,13].…”
Section: Sample Preparationmentioning
confidence: 99%